Gerakan Moderasi Islam Dalam Perspektif Deteksi Dini: Studi Gerakan Pemuda Ansor Kota Kediri - Subakir, Ahmad; Mustamir, Ahmad Khoirul (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This study discusses radicalism and deradicalism, and the Youth Movement (GP Ansor) which seized the attention of researchers and academics. They put up a fight by using the perspective of moderatism based on Ahlussunah wal Jamaah aN Nahdliyah and Indonesian values. This perspective was also carried out by all members of the Board of Management of the Ansor Youth Movement (PC GP Ansor) of Kediri City. This research is descriptive qualitative research with a case study approach. The results of this study indicate that GP Ansor of Kediri City is able to carry out resistance and early detection of radicalism in the City of Kediri. They tried to take over public places and facilities to spread the idea of Islam Ahlussunnah Wal Jamaah An Nahdhiyah.